Comment on “Aroused by the odes, established by the rules of propriety, perfected by music: integrating aesthetic education in contemporary music education through Confucian aesthetic philosophy” - Ge Zhan (Trans/Form/Ação)
Commented article: YANG, Wenpeng. Aroused by the odes, established by the rules of propriety, perfected by music: integrating aesthetic education in contemporary music education through Confucian aesthetic philosophy. Trans/Form/Ação: revista de filosofia da Unesp, v. 47, n. 6, e02400318, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/16092.